Friendships among very young children in the daily life of Early Childhood Education (Práxis Educativa, 2025)
This article results from an ethnographic research study in the field of the Social Studies of Childhood, which investigated how three-year-old children express their friendships in Early Childhood Education. The data generation strategies included participant observation, field diary, voice recording, and the writing of episodes. Based on the analysis of the data, the following analytical units were defined: generalisms in the use of the term “friend” in adult mediations; affirmations in the children’s use of the term “friend”; children’s performative expressiveness in the use of the term “friend”; and children’s friendships in nuances. It is inferred that friendship is constituted through a dynamic of socialization that occurs in children’s play, peer conversations, interactions with adults, participation in planned activities, among other situations in which children recognize their friends in everyday social relations.Keywords: Early Childhood Education. Friendship. Socialization. Research with children.